The role of artificial intelligence in enhancing tax compliance and customs efficiency: A case study of the South African Revenue Service (SARS) - Brahmia, Nabil (International journal of economic perspectives, 2025)
The integration of Artificial Intelligence (AI) in tax administration and customs operations has become a transformative force in modern revenue services worldwide. However, in the context of South Africa, the adoption of AI by the South African Revenue Service (SARS) remains underexplored due to the lack of comprehensive open data and academic research. This study investigates the current state of AI implementation in SARS, analyzing available reports, IT infrastructure indicators, transparency levels, and cybersecurity readiness. Using a qualitative and analytical approach, this research identifies key challenges hindering the effective deployment of AI in SARS, including technological gaps, insufficient data infrastructure, and cybersecurity vulnerabilities. Furthermore, the study proposes a strategic framework for enhancing AI adoption, emphasizing improvements in IT modernization, data governance, and risk management protocols. Findings indicate that South Africa’s current technological and regulatory landscape lags behind global benchmarks, necessitating urgent reforms to harness AI’s full potential in tax compliance and customs efficiency. This paper contributes to the emerging discourse on AI in African tax administrations by providing one of the first systematic assessments of SARS’ AI readiness, offering actionable insights for policymakers and future research.